Curing composition, cured product and application thereof

By using the cured composition of specific epoxy monomer components and hardeners, a cured substance with low water absorption rate is formed, which solves the problem that the existing resin composition is easy to absorb moisture and generates bubbles at high temperatures, and improves the packaging yield of the electronic device.

CN119638956APending Publication Date: 2025-03-18DAXIN MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411274149.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-13
Filing Date
2024-09-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing sealing resin compositions are prone to moisture absorption during high-temperature reliability testing, resulting in bubble generation, which may cause bursting of electronic devices and affect packaging yield.

Method used

A cured composition containing specific epoxy monomer components and a hardener is used to form a cured substance with low water absorption through the curing reaction to ensure that no bubbles are generated at high temperatures.

Benefits of technology

The low water absorption rate and appropriate fluidity of the cured substance are achieved, the problem of electronic device burst caused by bubble generation is avoided, and the yield of electronic device after packaging is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638956A_ABST
    Figure CN119638956A_ABST
Patent Text Reader

Abstract

A curing composition includes an epoxy monomer component and at least one hardener. The epoxy monomer component is selected from a first component or a second component. The first component is composed of at least one first epoxy monomer shown in the formula (I), and the second component comprises at least one first epoxy monomer shown in the formula (I) and at least one second epoxy monomer different from the first epoxy monomer shown in the formula (I). When the total amount of the epoxy monomer component is 100 wt%, the total amount of the first epoxy monomer shown in the formula (I) is more than 25 wt% and less than 100 wt%, and the total amount of the second epoxy monomer is more than 0 wt% and less than 75 wt%. R1 represents an alkylene group of C1 to C3, R21 represents a single bond or oxygen, R22 represents an alkylene group of C1 to C3, R3 represents an alkylene group of C1 to C3, R4 represents hydrogen or an alkyl group of C1 to C3, R5 represents hydrogen or an alkyl group of C1 to C3, and R6 represents hydrogen or an alkyl group of C1 to C3. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a semiconductor field, and in particular to a solidified composition, a solidified material and applications thereof. Background Art

[0002] Chinese Patent Publication No. 110036070 discloses a sealing resin composition, which includes 10wt% to 50wt% of epoxy resin, 1wt% to 50wt% of a curing agent having an amino group, less than 3wt% of a resin having a phenoxy structure, and 40wt% to 85wt% of an inorganic filler. The epoxy resin is, for example, an o-cresol novolac epoxy resin, a glycidyl ester epoxy resin, or a glycidyl amine epoxy resin. The glycidyl amine epoxy resin is, for example, para-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline (triglycidyl p-aminophenol). The sealing resin composition has a viscosity of 0.1Pa·s to 100Pa·s at 25°C and has appropriate fluidity, so that it can be filled in the gap between the carrier board (e.g., a metal wire substrate) and the electronic component (e.g., a semiconductor chip) of the electronic device by the principle of capillary action, thereby encapsulating the electronic device.

[0003] Although the sealing resin composition has appropriate fluidity and can be used as a bottom filling material for flip chips, the cured product formed by the sealing resin composition has the property of being easily hygroscopic, so that during high-temperature reliability testing, water vapor in the cured product is easily generated into bubbles. The presence of bubbles makes the packaged electronic device prone to bursting. In such a case, the packaged electronic device is likely to have a poor yield problem.

[0004] In view of the above, for those skilled in the art of electronic device packaging, developing a material having appropriate fluidity and capable of forming a cured product with low hygroscopicity is an urgent problem to be solved. Summary of the invention

[0005] Therefore, a first object of the present invention is to provide a curing composition having appropriate fluidity and capable of forming a cured product with low water absorption.

[0006] Therefore, the curing composition of the present invention comprises an epoxy monomer component and at least one hardener. The epoxy monomer component is selected from a first component or a second component, wherein the first component is composed of at least one first epoxy monomer represented by formula (I), the second component comprises at least one first epoxy monomer represented by formula (I) and at least one second epoxy monomer different from the first epoxy monomer represented by formula (I), and based on the total amount of the epoxy monomer component being 100wt%, the total amount of the first epoxy monomer represented by formula (I) is greater than 25wt% and less than 100wt%, and the total amount of the second epoxy monomer is greater than 0wt% and less than 75wt%.

[0007]

[0008] Among them, R 1 represents a C1 to C3 alkylene group, R 21 represents a single bond or oxygen, R 22 represents a C1 to C3 alkylene group, R 3 represents a C1 to C3 alkylene group, R 4 represents hydrogen or a C1 to C3 alkyl group, R 5 represents hydrogen or a C1 to C3 alkyl group, and R 6 represents hydrogen or a C1 to C3 alkyl group.

[0009] The second object of the present invention is to provide a cured product.

[0010] The cured product of the present invention is formed by a curing reaction of the above-mentioned curable composition.

[0011] The third object of the present invention is to provide a use of the above-mentioned cured composition and the above-mentioned cured product as an underfill material.

[0012] The efficacy of the present invention is that the curing composition of the present invention has a low viscosity and proper fluidity through the first epoxy monomer represented by formula (I), and the cured product formed by the curing composition has a low water absorption rate, so that during high-temperature reliability testing, there will be no problem of the packaged electronic device being prone to bursting due to the presence of bubbles, resulting in a good yield of the packaged electronic device. DETAILED DESCRIPTION

[0013] The present invention will be described in detail below.

[0014] [Curing composition]

[0015] The curing composition of the present invention comprises an epoxy monomer component and at least one hardener. The epoxy monomer component is selected from a first component or a second component, wherein the first component is composed of at least one first epoxy monomer represented by formula (I), the second component comprises at least one first epoxy monomer represented by formula (I) and at least one second epoxy monomer different from the first epoxy monomer represented by formula (I), and based on the total amount of the epoxy monomer component being 100wt%, the total amount of the first epoxy monomer represented by formula (I) is greater than 25wt% and less than 100wt%, and the total amount of the second epoxy monomer is greater than 0wt% and less than 75wt%.

[0016]

[0017] Among them, R 1 represents a C1 to C3 alkylene group, R 21 represents a single bond or oxygen, R 22 represents a C1 to C3 alkylene group, R 3 represents a C1 to C3 alkylene group, R 4 represents hydrogen or a C1 to C3 alkyl group, R 5 represents hydrogen or a C1 to C3 alkyl group, and R 6 represents hydrogen or a C1 to C3 alkyl group.

[0018] In some embodiments of the present invention, the total amount of the epoxy monomer component is 5wt% to 65wt% based on the total amount of the curing composition as 100wt%. In some embodiments of the present invention, the total amount of the epoxy monomer component is 20wt% to 65wt% based on the total amount of the curing composition as 100wt%.

[0019] In some embodiments of the present invention, the epoxy monomer component is the first component.

[0020] In some embodiments of the present invention, the first epoxy monomer represented by formula (I) is selected from

[0021]

[0022] In some embodiments of the present invention, the epoxy monomer component is the second component, and the second component includes at least one first epoxy monomer represented by formula (I) and at least one second epoxy monomer different from the first epoxy monomer represented by formula (I), and based on the total amount of the epoxy monomer component as 100wt%, the total amount of the first epoxy monomer represented by formula (I) is greater than 25wt% and less than 100wt%, and the total amount of the second epoxy monomer is greater than 0wt% and less than 75wt%. In some embodiments of the present invention, based on the total amount of the epoxy monomer component as 100wt%, the total amount of the first epoxy monomer represented by formula (I) is greater than 60wt% and less than 100wt%.

[0023] In order to give the cured product formed by the cured composition a higher glass transition temperature (glass transition temperature) and better adhesion strength, the second epoxy monomer is, for example, but not limited to, an epoxy monomer having two epoxy groups and multiple aromatic rings. The epoxy monomer having two epoxy groups and multiple aromatic rings is, for example, but not limited to etc. In, X 1 and X 2 represents a C1 to C3 alkylene group, and X 3 and X 4 is represented by hydrogen or methyl. For example, but not limited to, bisphenol F diglycidyl ether, bisphenol A diglycidyl ether or In some embodiments of the present invention, the second epoxy monomer is an epoxy monomer having two epoxy groups and multiple aromatic rings. In some embodiments of the present invention, the epoxy monomer having two epoxy groups and multiple aromatic rings is selected from

[0024]

[0025] The hardener may be used alone or in combination, and the hardener may be, for example, but not limited to, an aniline hardener, an acid anhydride hardener, or a phenolic hardener. The aniline hardener may be, for example, but not limited to, aniline, 4,4'-methylenebis(2-ethylaniline), 4,4'-methylenebis(2-methyl-6-ethylaniline), or 4-methyl-2,6-bis(methylsulfanyl)benzene-1,3-diamine. The anhydride hardener is, for example, but not limited to, 4,5-dimethyl-7-(2-methyl-1-propen-1-yl)-3a,4,7,7a-tetrahydro-2-benzofuran-1,3-dione. The phenolic hardener is, for example, but not limited to, 4,4'-methylenebis(2-allylphenol). In some embodiments of the present invention, the hardener is selected from aniline hardeners, anhydride hardeners, or phenolic hardeners. In some embodiments of the present invention, based on 100wt% of the total amount of the curing composition, the total amount of the hardener is 11wt% to 60wt%. In some embodiments of the present invention, based on 100 wt % of the total amount of the curing composition, the total amount of the hardener is 11 wt % to 45 wt %.

[0026] In some embodiments of the present invention, the solidified composition further comprises at least one filler. The filler is, for example, but not limited to, spherical silica or alumina. In some embodiments of the present invention, the filler is selected from spherical silica or alumina. In some embodiments of the present invention, the total amount of the filler is greater than 0wt% and less than 70wt%, based on the total amount of the solidified composition as 100wt%. In some embodiments of the present invention, the total amount of the filler is 55wt% to 70wt%, based on the total amount of the solidified composition as 100wt%.

[0027] [cured material]

[0028] The solidified material is formed by a solidified composition undergoing a solidification reaction. The solidified composition is as described above, so it is not described in detail. In some embodiments of the present invention, the temperature range of the solidification reaction is 100° C. to 200° C., and the time range is 0.5 hour to 3 hours.

[0029] [use]

[0030] One of the curing composition and the cured product may be used as an underfill material.

[0031] One of the solidified composition and the solidified material is used as a bottom filling material disposed between a carrier and a semiconductor element of a semiconductor device to encapsulate the semiconductor device. The carrier is, for example, but not limited to, a printed circuit board, a ceramic substrate, or a metal wire substrate. The semiconductor element is, for example, but not limited to, a light emitting diode chip or an integrated circuit chip.

[0032] The present invention will be further described with reference to the following examples, but it should be understood that the examples are only for illustration and should not be construed as limitations of the present invention.

[0033] Example 1

[0034] 22.5 wt% of the first epoxy monomer mixture [comprising 14.42 wt% and 8.08wt% and 8.1 wt % of bisphenol F diglycidyl ether (as a second epoxy monomer) to form an epoxy monomer component (i.e., a second component), wherein the total amount of the first epoxy monomer in the epoxy monomer component is 73.5 wt %. Then, 14.4 wt % of a hardener mixture [comprising 9.36 wt % of 4,4'-methylenebis(2-ethylaniline) and 5.04 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline)] and 55 wt % of spherical silica are mixed with the epoxy monomer component to obtain a cured composition.

[0035] Examples 2 to 3

[0036] The preparation methods of Examples 2 to 3 are substantially the same as those of Example 1, with the main difference being that the types or amounts of the components are changed. In Example 2, the first epoxy monomer mixture comprises 8.84 wt % of and 4.96wt% The hardener mixture includes 8.06 wt% of 4,4'-methylenebis(2-ethylaniline) and 4.34 wt% of 4,4'-methylenebis(2-methyl-6-ethylaniline). In Example 3, the first epoxy monomer mixture includes 25.19 wt% of and 14.11wt% The hardener mixture includes 23.2 wt % of 4,4'-methylenebis(2-ethylaniline) and 12.50 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline).

[0037] Example 4

[0038] 36.47wt% and 20.43wt% Then, 43.1 wt % of a hardener mixture (including 28.015 wt % of 4,4'-methylenebis(2-ethylaniline) and 15.085 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline)) was mixed with the epoxy monomer component to obtain a cured composition.

[0039] Example 5

[0040] 18.91wt% and 10.59wt% Then, 15.5 wt % of a hardener mixture (including 10.075 wt % of 4,4'-methylenebis(2-ethylaniline) and 5.425 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline)) and 55 wt % of spherical silica were mixed with the epoxy monomer component to obtain a cured composition.

[0041] Examples 6 to 8

[0042] The preparation methods of Examples 6 to 8 are substantially the same as those of Example 1, with the main difference being that the types or amounts of the components are changed. In Example 6, the first epoxy monomer mixture comprises 3.91 wt% of and 2.19wt% The hardener mixture includes 7.77 wt% of 4,4'-methylenebis(2-ethylaniline) and 4.18 wt% of 4,4'-methylenebis(2-methyl-6-ethylaniline). In Example 7, the first epoxy monomer mixture includes 3.90 wt% of and 2.18wt% The hardener mixture includes 7.42 wt% of 4,4'-methylenebis(2-ethylaniline) and 4.00 wt% of 4,4'-methylenebis(2-methyl-6-ethylaniline). In Example 8, the first epoxy monomer mixture includes 3.78 wt% of and 2.12wt% The hardener mixture includes 8.00 wt % of 4,4'-methylenebis(2-ethylaniline) and 4.30 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline).

[0043] Example 9

[0044] 5.90 wt% of the first epoxy monomer mixture [containing 3.78 wt% and 2.12wt% 0.58wt% (as the second epoxy monomer), 8.00 wt% (as the second epoxy monomer) and 8.87 wt% The epoxy monomer component (i.e., the second component) is mixed with 11.65 wt % of a hardener mixture (including 7.57 wt % of 4,4'-methylenebis(2-ethylaniline) and 4.08 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline)) and 65 wt % of spherical silica to obtain a cured composition.

[0045] Comparative Example 1

[0046] 8.1 wt% of bisphenol F diglycidyl ether and 22.5 wt% of para-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline were mixed to form an epoxy monomer component. Then, 14.4 wt% of a hardener mixture [including 9.36 wt% of 4,4'-methylenebis(2-ethylaniline) and 5.04 wt% of 4,4'-methylenebis(2-methyl-6-ethylaniline)] and 55 wt% of spherical silica were mixed with the epoxy monomer component to obtain a cured composition.

[0047] Comparative Examples 2 to 6

[0048] The preparation methods of Comparative Examples 2 to 6 are substantially the same as those of Comparative Example 1, with the main difference being that the types or amounts of the components are changed. In Comparative Example 2, the hardener mixture comprises 7.865 wt % of 4,4'-methylenebis(2-ethylaniline) and 4.235 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline). In Comparative Example 3, the hardener mixture comprises 22.62 wt % of 4,4'-methylenebis(2-ethylaniline) and 12.18 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline). In Comparative Example 4, the hardener mixture comprises 27.365 wt % of 4,4'-methylenebis(2-ethylaniline) and 14.735 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline). In Comparative Example 5, the hardener mixture includes 5.785 wt % of 4,4'-methylenebis(2-ethylaniline) and 3.115 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline). In Comparative Example 6, the hardener mixture includes 10.075 wt % of 4,4'-methylenebis(2-ethylaniline) and 5.425 wt % of 4,4'-methylenebis(2-methyl-6-ethylaniline).

[0049] Evaluation Project

[0050] Viscosity (unit: Pa·s) measurement: 0.55 ml of the cured composition of the embodiment and the comparative example was placed in a rheometer (brand: TA; model: AR2000ex) and subjected to a shear rate of 1 s at 25°C and 100°C. -1 Take measurements.

[0051] Water absorption (unit: %) measurement: The curing composition of the embodiment and the comparative example was subjected to a curing reaction at 150° C. for 2 hours to form a 0.8×0.8 cm 2 Then, the block-shaped solidified product was placed in an oven set at a temperature of 150°C for 1 hour for drying, and a plurality of dried products were obtained, and the dried products were weighed and recorded as W0. Next, the dried products were placed in a high-pressure accelerated aging machine (pressure cooker tester; brand: kson; model: HAST-APLUS), and left to stand for 20 hours at a temperature of 120°C and a relative humidity of 100%, and then weighed and recorded as W1. The water absorption rate is {[(W1-W0) / W0] / (amount of epoxy monomer component + amount of hardener)}×100%.

[0052] Adhesion (unit: kgf / mm 2) Measurement: The curing composition of the embodiment and the comparative example is coated on a silicon carrier to form a plurality of cylindrical protrusions, and then, the cylindrical protrusions are subjected to a curing reaction at 150°C for 2 hours to form a plurality of cylindrical cured products with a diameter of 0.4 mm and a height of 0.1 mm. Then, the cylindrical cured products are placed in a thrust machine (brand: Nordson; model: DAGE 4000PXY), and then, at 22°C, different lateral forces from small to large are applied to each cylindrical cured product, and the lateral forces at the time of fracture are recorded, and then, the room temperature adhesion is calculated. Then, the cylindrical cured products are placed in an environment of 110°C for 2 minutes, and then, different lateral forces from small to large are applied to each cylindrical cured product, and the lateral forces at the time of fracture are recorded, and then, the high temperature adhesion is calculated.

[0053] Table 1

[0054]

[0055] Table 2

[0056]

[0057] Table 3

[0058]

[0059] Table 4

[0060]

[0061] From the experimental results of Examples 1 to 4 and Comparative Examples 1 to 4 in Table 4, it can be seen that the viscosity of the curing composition of Examples 1 to 4 at 25°C is lower than that of the curing composition of Comparative Examples 1 to 4, respectively. Furthermore, from the experimental results of Example 5 and Comparative Example 6 in Table 4, it can be seen that the viscosity of the curing composition of Example 5 at 25°C is lower than that of the curing composition of Comparative Example 6. Therefore, it can be seen that the curing composition of the present invention comprising the first epoxy monomer represented by formula (I) does have better fluidity.

[0062] Furthermore, the water absorption rates of the cured products formed by the cured compositions of Examples 1 to 4 are lower than those of the cured products of Comparative Examples 1 to 4, and are lower than 4.5wt% {[(4.00-3.82) / 4.00]×100wt%}, 4.28wt% {[(2.57-2.46) / 2.57]×100wt%}, 17.65wt% {[(0.68-0.56) / 0.68]×100wt%} and 16.05wt% {[(2.43-2.04) / 2.43]×100wt%}, respectively. This indicates that the cured product formed by the cured composition comprising the first epoxy monomer represented by formula (I) of the present invention does not have the problem of easily bursting the packaged electronic device due to the presence of bubbles during reliability testing at high temperature, so that the packaged electronic device has a good yield.

[0063] In addition, from the experimental results of Examples 6 to 9 and Comparative Example 5 in Table 4, it can be seen that the viscosity of the curing compositions of Examples 6 to 9 at 25° C. is lower than that of the curing composition of Comparative Example 5, and the water absorption of the cured products formed by the curing compositions of Examples 6 to 9 is also lower than that of the cured product of Comparative Example 5. Therefore, it can be seen that the curing compositions of the present invention comprising the first epoxy monomer represented by formula (I) and different second epoxy monomers can meet the requirements of appropriate fluidity, and the cured products formed by the curing compositions can also meet the requirements of low water absorption.

[0064] In summary, through the first epoxy monomer represented by formula (I), the curing composition of the present invention has a lower viscosity and has appropriate fluidity, and the cured product formed by the curing composition has a lower water absorption rate, so that during the reliability test at high temperature, there will be no problem of the packaged electronic device being prone to bursting due to the presence of bubbles, resulting in the packaged electronic device having a good yield, so the purpose of the present invention can be achieved.

[0065] However, the above are only embodiments of the present invention and should not be used to limit the scope of the present invention. All simple equivalent changes and modifications made according to the claims and the patent specification of the present invention are still within the scope of the present patent.

Claims

1. A curing composition comprising: The epoxy monomer component is selected from a first component or a second component, wherein the first component is composed of at least one first epoxy monomer represented by formula (I), and the second component includes at least one first epoxy monomer represented by formula (I) and at least one second epoxy monomer different from the first epoxy monomer represented by formula (I), and based on the total amount of the epoxy monomer component being 100wt%, the total amount of the first epoxy monomer represented by formula (I) is greater than 25wt% and less than 100wt%, and the total amount of the second epoxy monomer is greater than 0wt% and less than 75wt%, and at least one aniline hardener, in, R 1 represents a C1 to C3 alkylene group, R 21 represents a single bond or oxygen, R 22 represents a C1 to C3 alkylene group, R 3 represents a C1 to C3 alkylene group, R 4 represents hydrogen or a C1 to C3 alkyl group, R 5 represents hydrogen or a C1 to C3 alkyl group, and R 6 represents hydrogen or a C1 to C3 alkyl group.

2. The curable composition according to claim 1, wherein The first epoxy monomer represented by formula (I) is selected from 3. The curable composition according to claim 1, wherein The epoxy monomer component is the first component.

4. The curable composition according to claim 1, wherein The epoxy monomer component is the second component.

5. The curable composition according to claim 4, wherein Based on 100 wt % of the total amount of the epoxy monomer component, the total amount of the first epoxy monomer represented by formula (I) is greater than 60 wt % and less than 100 wt %.

6. The curable composition according to any one of claims 1 to 5, wherein Based on 100 wt % of the total amount of the curing composition, the total amount of the epoxy monomer component is 5 wt % to 65 wt %.

7. The curable composition according to claim 1, wherein The second epoxy monomer is an epoxy monomer having two epoxy groups and a plurality of aromatic rings.

8. The curable composition according to claim 7, wherein: The epoxy monomer having two epoxy groups and multiple aromatic rings is selected from X 1 and X 2 represents a C1 to C3 alkylene group, and X 3 and X 4 It is represented by hydrogen or methyl.

9. The curable composition according to claim 1, further comprising at least one filler.

10. The curable composition according to claim 9, wherein Based on 100 wt % of the total amount of the curing composition, the total amount of the filler is greater than 0 wt % and less than 70 wt %.

11. The curable composition according to claim 9, wherein The filler is selected from spherical silica or alumina.

12. A cured product formed by a curing reaction of the curable composition according to any one of claims 1 to 11.

13. Use of one of the cured composition according to any one of claims 1 to 11 and the cured product according to claim 12 as an underfill material.

14. The use according to claim 13, wherein One of the solidified composition and the solidified material is used as a bottom filling material arranged in a gap between a carrier and a semiconductor element of a semiconductor device to encapsulate the semiconductor device.